Safety and efficacy of intravenous thrombolytic therapy in the extended window up to 24 hours: A systematic review and meta‐analysis - Omar M. Al‐Janabi; Seyed Behnam Jazayeri; Michelle A. Toruno; Yamama M. Mahmood; Sherief Ghozy; Shadi Yaghi; Alejandro A. Rabinstein; David F. Kallmes (Annals of Clinical and Translational Neurology)
Abstract Objective About 25% of patients with acute ischemic stroke (AIS) present within the intravenous thrombolytic (IVT) therapeutic window of <4.5 h. This study is to elucidate the safety and efficacy of IVT in the extended therapeutic window (ETW) in patients with AIS. Methods Using PRISMA guidelines, a systematic review was conducted using PubMed, Embase, and Scopus. A rigorous risk of bias assessment was conducted using the RoB2 tool. Rates of excellent and good functional outcome (mRS 0–1 and mRS 0–2) at 90 days, symptomatic intracranial hemorrhage (sICH), and mortality at 90 days were pooled using generalized linear mixed model and compared with controls. Meta‐analyses were conducted employing random‐effect models with risk ratio (RR) and 95% confidence intervals (CIs). Subgroup analysis was performed to assess the effect of imaging modalities used for patient selection. Results Eight randomized controlled trials (n = 2221, 59% male) were included. At 90 days IVT showed higher rates of functional recovery: mRS 0–1: RR 1.21 95% CI 1.1–1.34, p < 0.001, and mRS 0–2: RR 1.11 95% CI 1.03–1.18, p = 0.004. Rate of mortality at 90 day was not different between groups: RR 1.17 95% CI 0.93–1.48, p = 0.17. However, the rate of sICH was higher among IVT group: RR 2.93 95% CI 1.53–5.6, p = 0.001. Subgroup analysis showed higher mRS 0–1 among patients who were selected based on perfusion imaging (p < 0.05). Interpretation The use of IVT in AIS in ETW is beneficial especially with the use of perfusion imaging for patients' selection.